Air–sea–ice interactions in Isfjorden, Svalbard: An atmospheric perspective. - Frank, L.; Jonassen, M. O.; Skogseth, R.; Vihma, T. (John Wiley & Sons, 2025)
Based on the high-resolution Copernicus Arctic Regional Reanalysis (CARRA), this study investigates spatio-temporal variations in air–sea heat exchange in Isfjorden, Svalbard, during 2011–2021. Turbulent heat fluxes are found to be the main driver of interannual variability in the net air–sea heat exchange. The complex terrain surrounding Isfjorden leads to large spatial variability in turbulent heat fluxes during the cooling season. The spatial variability is driven by sea ice insulating parts of the fjord surface from the atmosphere, and by orographic effects such as wind channeling and localized advection of cold and dry air masses originating from snow- and ice-covered land areas. Interannual variability is caused mainly by differences in near-surface temperatures. Compared with Isfjorden, the annual net heat loss from the ocean to the atmosphere is larger in a nearby open-ocean reference area in the Fram Strait, where the driving gradients and wind speed are generally larger, the sea surface is warmer, and no sea ice is present. However, spatial variations are small in this reference area.